1998
DOI: 10.1016/s1385-1101(97)00060-9
|View full text |Cite
|
Sign up to set email alerts
|

The hydrography and biology of a bloom of the coccolithophorid Emiliania huxleyi in the northern North Sea

Abstract: In June=July 1994 a study was made of a small bloom of the coccolithophorid Emiliania huxleyi in an area of the North Sea to the east of the Shetland Islands. Observations on the hydrography of the study area indicated the bloom was associated with Atlantic water and was confined to an area in which a stable shallow mixed layer had formed. There was no evidence to suggest association of horizontal physical structure with the bloom development. High cell densities of >1-6 ð 10 6 cells dm 3 , together with low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
5
25
2
Order By: Relevance
“…The PIC:POC ratio ranged between 0.23 and 0.66, except at station 7 ( $0.10) and in the surface sample at station 1 ( $0.20). Values of the PIC:POC ratio were higher than those reported in the same area (0.20-0.30) in June 2004 and in the North Sea in June 1994 (o0.25; Head et al, 1998).…”
Section: Biogeochemical Settings In June 2006contrasting
confidence: 64%
See 2 more Smart Citations
“…The PIC:POC ratio ranged between 0.23 and 0.66, except at station 7 ( $0.10) and in the surface sample at station 1 ( $0.20). Values of the PIC:POC ratio were higher than those reported in the same area (0.20-0.30) in June 2004 and in the North Sea in June 1994 (o0.25; Head et al, 1998).…”
Section: Biogeochemical Settings In June 2006contrasting
confidence: 64%
“…The CAL to PP ratio (CAL:PP, Table 2) varied considerably from one station to another, ranging from 0.01 (station 8 at 20 m) to 1.13 (station 4bis at 3 m). The average CAL:PP ratio (0.29 70.25; n ¼18) during our cruise was higher than that reported in the Bay of Biscay in June 2004 (range 0.02-0.31; average 0.16 (n¼11); Harlay et al, 2010), than in the North Sea in July 1993 (0.03-0.18; van der Wal et al, 1995) and June 1994 (0.14-0.16; Head et al, 1998), and off Iceland in June 1991 (0.14-0.19; Ferná ndez et al, 1993).…”
Section: Biogeochemical Settings In June 2006contrasting
confidence: 59%
See 1 more Smart Citation
“…Bernardi Aubry et al (2006) found E. huxleyi to be typical for the mixing period and summer deep waters in the northern Adriatic Sea. This coccolithophorid is ubiquitous in both coastal and oceanic waters and regularly forms extensive blooms, particularly at mid-latitudes (Head et al, 1998).…”
Section: Seasonal Succession Of the Phytoplankton Speciesmentioning
confidence: 99%
“…Fe, Zn, and Mn) have been shown to influence coccolithophore physiology and control phytoplankton community assemblage to various extents (Nanninga and Tyrrell, 1996;Zondervan, 2007;Boyd et al, 2010, and references therein). However, only few studies have described the structure and the spatial and temporal dynamics of phytoplankton communities during these blooms along the western European continental margin (Head et al, 1998;Joint et al, 2001;Fileman et al, 2002;Lampert et al, 2002). This information is needed, as the importance of the phytoplankton community structure to the biological pump is still poorly understood (Smythe- Wright et al, 2010, and references therein).…”
Section: Introductionmentioning
confidence: 99%